Biotinylated subunit of 3-methylcrotonyl-CoA carboxylase encoding gene (AtMCCA) participating in Arabidopsis resistance to carbonate Stress by transcriptome analysis. (February 2022) - Wang, Yao; Ye, Xiaoxue; Takano, Tetsuo; Liu, Shenkui; Bu, Yuanyuan
Highlights: We analyzed transcriptome of the shoot and root part of wild-type Arabidopsis treated with 3 mM NaHCO3 at different times. We identified a total of six DEGs with a up-regulation by NaHCO3 stress in the result of qRT-PCR and RNA-Seq. The ability of AtMCCA to resist carbonate stress was verified by phenotypic experiment which was enhanced with biotin. Abstract: Soil salinization is a major factor impacting modern agricultural production, and alkaline soils contain large amounts of NaHCO3 . Therefore, understanding plant tolerance to high levels of NaHCO3 is essential. In this study, a transcriptome analysis of shoot and root tissues of wild-type Arabidopsis thaliana was conducted at 0, 4, 12, 24 and 48 h after exposure to a 3 mM NaHCO3 stress. We focused on differentially expressed genes (DEGs) in roots identified in the early stages (4 h and 12 h) of the NaHCO3 stress response that were enriched in GO term, carboxylic acid metabolic process, and utilize HCO3 − . Six genes were identified that exhibited similar expression patterns in both the RNA-seq and qRT-PCR data. We also characterized the phenotypic response of AtMCCA-overexpressing plants to carbonate stress, and found that the ability of AtMCCA-overexpressing plants to tolerate carbonate stress was enhanced by the addition of biotin to the growth medium.